2012
DOI: 10.1085/jgp.201210899
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells used to reveal drug actions in a long QT syndrome family with complex genetics

Abstract: Understanding the basis for differential responses to drug therapies remains a challenge despite advances in genetics and genomics. Induced pluripotent stem cells (iPSCs) offer an unprecedented opportunity to investigate the pharmacology of disease processes in therapeutically and genetically relevant primary cell types in vitro and to interweave clinical and basic molecular data. We report here the derivation of iPSCs from a long QT syndrome patient with complex genetics. The proband was found to have a de no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(133 citation statements)
references
References 44 publications
9
124
0
Order By: Relevance
“…Preliminary experimental and clinical evidences claim that mexiletine, a sodium channel blocker targeted in the inactivated state [26], could preferentially reduce the elevated late I Na [27] and shorten the APD in a cellular model of LQT3 [28,29] and the QT interval in LQT3 patients [30,31]. Liu et al reported that mexiletine produces more significant QRS widening when APD prolongation is induced by late I Na enhancer than I Kr blocker in the rabbit ventricular wedges, which indicates that the enhanced late I Na may be the consequence due to the failure of fast Na channel inactivation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experimental and clinical evidences claim that mexiletine, a sodium channel blocker targeted in the inactivated state [26], could preferentially reduce the elevated late I Na [27] and shorten the APD in a cellular model of LQT3 [28,29] and the QT interval in LQT3 patients [30,31]. Liu et al reported that mexiletine produces more significant QRS widening when APD prolongation is induced by late I Na enhancer than I Kr blocker in the rabbit ventricular wedges, which indicates that the enhanced late I Na may be the consequence due to the failure of fast Na channel inactivation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include long‐QT syndrome (Terrenoire et al , 2013; Malan et al , 2016), catecholaminergic polymorphic ventricular tachycardia (Penttinen et al , 2015) and heart failure with preserved ejection fraction (Raphael et al , 2016). The cardiotoxic effects of anthracyclines in cardio‐oncology (Burridge et al , 2016) have also been recently validated (Avior et al , 2016).…”
Section: Cardiotoxicity Screening Methodologiesmentioning
confidence: 99%
“…In a LQT3 patient with both a de novo F1473C SCN5A mutation and a K897T KCNH2 gene polymorphism, the APDs of LQT3 hiPSC-CMs via a current clamp were not measurable because of a relatively depolarized diastolic membrane potential in these immature hiPSC-CMs. 66 Fatima et al likewise had difficulty showing increased ADP in LQT3 hiPSC-CMs derived from patients carrying different SCN5A mutations (p.V240M and p.R535Q) because of variations in the EP parameters among individual hiPSC-CMs. 68 These findings underscored the current limitations of hiPSC models, including the inability to accurately recapitulate all clinical disease thus far.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 99%